HIGH FAT DIET INDUCES LUNG REMODELING IN APOE DEFICIENT MICE: AN ASSOCIATION WITH AN INCREASE IN CIRCULATORY AND LUNG INFLAMMATORY FACTORS - Naura, Amarjit S. (2009)
Hypercholesterolemia is increasingly considered the basis for not only cardiovascular pathologies but also several complications affecting other organs including lungs. Here, we examined the effect of hypercholesterolemia on lung integrity using a mouse model (ApoE(−/−)) of high fat (HF) diet-induced atherosclerosis. A twelve-week HF diet regimen induced systemic production of TNF-α, IFN-γ, GMC-SF, RANTES, IL-1α, IL-2, and IL-12 with TNF–α as the predominant cytokine in ApoE(−/−) mice. Concomitantly, TNF-α, IFN-γ, and MIP-1α were detected in brochoalveolar lavage fluids of these mice, coinciding with lung inflammation consisting primarily of monocytes/macrophages. Such lung inflammation correlated with marked collagen deposition and an increase in matrix metalloproteinase-9 activity in ApoE(−/−) mice without mucus production. Although TGF-β1 was undetectable in brochoalveolar lavage fluid of ApoE(−/−) mice on HF diet, it displayed a much wider tissue distribution compared to that of control animals. Direct exposure of smooth muscle cellsto oxidized-LDL, in vitro, induced a time-dependent expression of TNF-α. Direct intratracheal TNF–α-administration induced a lung inflammation pattern in wild-type mice that was strikingly similar to that induced by HF diet in ApoE(−/−) mice. TNF–α administration induced expression of several factors known to be critically involved in lung remodeling including MCP-1, IL-1β, TGF–β1, adhesion molecules, collagen type-1, and TNF–α itself in the lungs of treated mice. These results suggest that hypercholesterolemia may promote chronic inflammatory conditions in lungs that are conducive to lung remodeling potentially through TNF–α-mediated processes.